Diagnostic performance of convex probe EBUS-TBNA in patients with mediastinal and coexistent endobronchial or peripheral lesions. Issue 50 (December 2016) - Verma, Akash; Goh, Kee San; Phua, Chee Kiang; Sim, Wen Yuan; Tee, Kuan Sen; Lim, Albert Y.H.; Tai, Dessmon Y.H.; Goh, Soon Keng; Kor, Ai Ching; Ho, Benjamin; Lew, Sennen J.W.; Abisheganaden, John
Abstract : Abstract: To compare the performance of convex probe endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) with conventional endobronchial biopsy (EBB) or transbronchial lung biopsy (TBLB) in patients with mediastinal, and coexisting endobronchial or peripheral lesions. Retrospective review of records of patients undergoing diagnostic EBUS-TBNA and conventional bronchoscopy in 2014. A total of 74 patients had mediastinal, and coexisting endobronchial or peripheral lesions. The detection rate of EBUS-TBNA for mediastinal lesion >1 cm in short axis, EBB for visible exophytic type of endobronchial lesion, and TBLB for peripheral lesion with bronchus sign were 71%, 75%, and 86%, respectively. In contrast, the detection rate of EBUS-TBNA for mediastinal lesion ⩽1 cm in short axis, EBB for mucosal hyperemia type of endobronchial lesion, and TBLB for peripheral lesion without bronchus sign were 25%, 63%, and 38%, and improved to 63%, 88%, and 62% respectively by adding EBB or TBLB to EBUS-TBNA, and EBUS-TBNA to EBB or TBLB. Postprocedure bleeding was significantly more common in patients undergoing EBB and TBLB 8 (40%) versus convex probe EBUS-TBNA 2 patients (2.7%, P  = 0.0004). EBUS-TBNA is a safer single diagnostic technique compared with EBB or TBLB in patients with mediastinal lesion of >1 cm in size, and coexisting exophytic type of endobronchial lesion, or peripheral lesion with bronchus sign. However, it requires combining with EBB or TBLB and vice versa to optimize yield when mediastinal lesion is ⩽1 cm in size, and coexisting endobronchial and peripheral lesions lack exophytic nature, and bronchus sign, respectively.